Instrumental Timed Up and Go test discloses abnormalities in patients with Cervical Dystonia. (December 2021) - Celletti, C.; Ferrazzano, G.; Belvisi, D.; Ferrario, C.; Tarabini, M.; Baione, V.; Fabbrini, G.; Conte, A.; Galli, M.; Camerota, F.
Abstract: Background Cervical dystonia is a movement disorder characterized by involuntary and sustained contraction of the neck muscles that determines abnormal posture. The aim of this study was to investigate whether dystonic posture in patients with cervical dystonia affects walking and causes postural changes. Methods Patients with cervical dystonia and a group of age-matched healthy controls underwent an instrumental evaluation of the Timed Up and Go Test. Findings All the spatio-temporal parameters of the sub-phases of the Timed up and go test had a significantly higher duration in cervical dystonia patients compared to the control group while no differences in flection and extension angular amplitudes were observed. Indeed, we found that Cervical Dystonia patients had abnormalities in turning, as well as in standing-up and sitting-down from a chair during the Timed up and go test than healthy controls. Interpretation Impairment in postural control in cervical dystonia patients during walking and postural changes prompts to develop rehabilitation strategies to improve postural stability and reduce the risk of fall in these patients. Highlights: Inertial sensors are useful to evaluate postural and walking functional test. Cervical Dystonia patients have higher duration in Time Up and Go test. Timed Up and Go alterations may be linked to deranged sensorimotor network of dystonia.